2022
DOI: 10.3390/microorganisms10101931
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan Parasites in Adult Dairy Small Ruminants and Potential Predictors for Their Presence in Faecal Samples

Abstract: There is a scope to study protozoan infections in adult ewes and does, as these animals can act as reservoirs of infection for lambs and kids, for which these pathogens are harmful. The objectives of this study were to describe the prevalence of protozoan infections in faecal samples from adult sheep and goats on dairy farms across Greece and to evaluate farm-related factors potentially associated with the presence of protozoan infections in these animals. A cross-sectional study was performed on 325 sheep and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous studies in Greece have reported a high frequency of Eimeria spp. detection in other animal species: poultry (85.7%) [44], small ruminants (69%) [45] and fish (67.3%) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Greece have reported a high frequency of Eimeria spp. detection in other animal species: poultry (85.7%) [44], small ruminants (69%) [45] and fish (67.3%) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Four bulk-tank samples were collected from the tank of each farm. Faecal samples were subsequently obtained from the female animals (ewes/does) on each farm [ 14 ]. Faecal samples were obtained directly from the rectum of animals, following the standard technique.…”
Section: Methodsmentioning
confidence: 99%
“…visited all the flocks for sample collection. Samples were collected directly from the rectum of adult ewes on the farms, as described in detail by Lianou et al [ 15 ]. In each flock, 20, 30, 40 or 50 ewes (for flocks with ≤165, 166–330, 331–500 or >500 ewes, respectively) were selected for sampling.…”
Section: Methodsmentioning
confidence: 99%